Purwarupa Sistem Deteksi COVID-19 Berbasis Website Menggunakan Algoritma Convolutional Neural Network - Ari Fadli; Yogi Ramadhani; Muhammad Syaiful Aliim (Ikatan Ahli Informatika Indonesia (IAII), 2021)
COVID-19 is a disease caused by coronavirus 2 (SARS-CoV-2). This virus belongs to the group of viruses that infect the respiratory system. Furthermore, the rapid rate of spread has made several countries implement a policy of implementing a lockdown to prevent the spread of this virus. In Indonesia, the government implemented the policy of